Educational robotics as a necessary element of training for the future of technological way - Sirenko, Svetlana N. (Journal of the Belarusian State University. Journalism, 2019)
The article explains the possibilities and the advisability of the inclusion educational robotics in the educational process of schools and higher education. The author reveals the meaning of the term «educational robotics». The developing potential of the new discipline as a powerful tool of training of graduates for life in the hightech environment, associated with the widespread introduction of robots is revealed. Pedagogical experience of the US, several European countries and the Russian Federation in the field of educational robotics is analyzed. The results of training the student teams for international competitions in robotics are summarized. Pedagogical work in this area is related to the problems of interdisciplinarity.